Innovation of Religious Moderation Education in Forming the Character of Tolerance and Interreligious Acceptance of Early Children in the Era of Society 5.0 - Samiaji, Mukhamad Hamid; Hafidz, Nur; Fatmawati, Emi (Islamic Studies Journal, 2023)
The presence of the Society 5.0 era make follow intolerance join in extends to children age early. Internalize moderation religious to child age early important for done in space education, so that participants educate capable own values moderate and have attitude acceptance good interfaith later day. Research purposes is for explore and discover innovation education moderation religious in form character tolerance and acceptance interfaith child age early in the era of society. Research methods use approach qualitative type studies case. Data collection techniques through observation, interviews and documentation. Data analysis techniques include data collection, data reduction, data presentation, withdrawal conclusion/verification of data, and testing the validity of the data. Research result show that innovation education moderation religious in form character tolerance and acceptance interfaith child age early at the PAUD PUHUA School Purwokerto institution packed through design curriculum based moderation religion, use technology and online learning, application education culture and values local, monitoring and evaluation aspect tolerance and acceptance interfaith, parental involvement, and building awareness technology and digital ethics